2023
DOI: 10.31387/oscm0550407
|View full text |Cite
|
Sign up to set email alerts
|

Key Directions for Transforming Supply Chain Management in Emerging Markets during the Post-COVID-19 Pandemic Period

Nail Israfilov,
Varvara Druzyanova,
Marina Ermakova
et al.

Abstract: This research aimed to identify the main directions for transforming supply chains in emerging markets to enable timely managerial responses to the challenges and opportunities during the post-COVID-19 pandemic period. The analysis of theoretical sources resulted in the formulation of the following research hypotheses: (H1) Sustainable development of supply chains in emerging markets during the post-COVID-19 pandemic period can be achieved through the digital transformation of supply chains; (H2) The most prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although the pandemic may be thought to have negatively affected the financial performance, some authors [49] have shown that increased demand for logistics services during the pandemic helped improve the performance of some companies in the logistics sector. Finally, in 2023, the papers have addressed more future-oriented topics, such as key directions for transforming SCM in emerging markets in the post-pandemic period [50]. Again, the theme of sustainability in relation to economic practices returns, emphasizing how circular-economy practices have been widely used in the pandemic period, in relation to the theme of resilience [51].…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Although the pandemic may be thought to have negatively affected the financial performance, some authors [49] have shown that increased demand for logistics services during the pandemic helped improve the performance of some companies in the logistics sector. Finally, in 2023, the papers have addressed more future-oriented topics, such as key directions for transforming SCM in emerging markets in the post-pandemic period [50]. Again, the theme of sustainability in relation to economic practices returns, emphasizing how circular-economy practices have been widely used in the pandemic period, in relation to the theme of resilience [51].…”
Section: Descriptive Statisticsmentioning
confidence: 99%